Evaluation of the accuracy of gait events detected using three different methods during running - Mo, S.-W.; Chow, D. H. K. (ISBS Proceedings Archive (Michigan), 2017)
Different methods have been proposed for determining initial contact and toe off with inertial measurement unit (IMU) attached to different anatomical positions. However, the accuracy has not yet been compared. This study aimed to evaluate the accuracy of three commonly used methods (S-, M-, and L-method) in detecting gait events at two running speed conditions (slow and fast). Obvious differences of detected initial contact and toe off and estimated stance duration among the three detection methods using IMU were found at the two running speed conditions. It was shown that initial contact detected using the S-method and toe off detected by the M-method were the best estimates of the gait events. Combined use of both methods is recommended for determining stance duration during overground running.